Sosialisasi Penggunaan Airbag Untuk Peluncuran Kapal Kayu di Kelurahan Galesong Kota, Kecamatan Galesong, Kabupaten Takalar - Ganding Sitepu; Lukman Bochary; Mohammad Rizal Firmansyah; Wihdat Djafar; Rosmani .; Suandar Baso; Indrawansyah .; Editya . (Faculty of Engineering UNHAS, 2024)
One of the centers for traditional wooden boat construction in South Sulawesi is Galesong District, Takalar Regency, South Sulawesi. Generally, wooden boats constructed by craftsmen in this area are for fishing. Craftsmen's skills in building the boat were acquired from their predecessors. However, the craftsmen still faced some problems during the boat construction work. One of the problems is related to launching the boat into the water, which is still conducted traditionally using logs and sandbags. The solution is to propose the use of airbags to launch ships. Airbags have been used to launch steel ships but relatively not for wooden boats. Hence, this activity aims to introduce the use of airbags to launch the boat. The target for the introduction is a group of wooden boat craftsmen,